Enhancing Cryptography Learning through Multimedia Based Instruction: Insights from Student Perceptions on Gather Platform - Siti Munirah Mohd; Muhammad Luthfil Hadi Mohd Hamadi; Muhammad Farhan Iman Muhamad Fuad; Muhammad Haziq Mohammad Iskandar Shah; Nakhma ‘Ussolikhah (Pena Cendekia Publishing, 2025)
Non-Indexed Publication